2010
DOI: 10.1002/ijc.24984
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic significance of iNOS in uveal melanoma

Abstract: Uveal melanoma (UM) is the most common primary intraocular tumor in adults. Disease metastasis occurs in half of the patients and is uniformly fatal despite systemic therapy. Inducible nitric oxide synthase (iNOS) is associated with disease progression in various malignancies including cutaneous melanoma. In this retrospective cohort, we examined the prognostic value of iNOS in UM by performing immunohistochemistry on paraffin-embedded sections of primary tumors (90 patients) and matched primary and metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…In particular, NOS2 favors IL-17 production by gd T cells that leads to the recruitment of PMN-MDSCs and subsequently to metastasis formation. As gd T cells from WT mice already display a higher capacity to produce IL-17 than their counterparts in NOS2KO mice at steady state, our data suggest that NOS2 predetermines gd T cell polarization toward a pro-tumor phenotype Global NOS2 expression has been associated with a poor prognosis in human cutaneous 21,22 as well as uveal 23 melanoma, but the mechanisms by which NOS2 is involved in tumor escape remains poorly explored. In Ret mice with a NOD genetic background, we have shown that the rapid tumor cell dissemination strongly correlates with a reduced dectin-1 expression on myeloid cells that is prevented by NOS2 inactivation.…”
Section: Discussionmentioning
confidence: 84%
“…In particular, NOS2 favors IL-17 production by gd T cells that leads to the recruitment of PMN-MDSCs and subsequently to metastasis formation. As gd T cells from WT mice already display a higher capacity to produce IL-17 than their counterparts in NOS2KO mice at steady state, our data suggest that NOS2 predetermines gd T cell polarization toward a pro-tumor phenotype Global NOS2 expression has been associated with a poor prognosis in human cutaneous 21,22 as well as uveal 23 melanoma, but the mechanisms by which NOS2 is involved in tumor escape remains poorly explored. In Ret mice with a NOD genetic background, we have shown that the rapid tumor cell dissemination strongly correlates with a reduced dectin-1 expression on myeloid cells that is prevented by NOS2 inactivation.…”
Section: Discussionmentioning
confidence: 84%
“…(Katušic and Vanhoutte 1986;Rubanyi and Vanhoutte 1986 a,b;Rubanyi 1988;Yanagishawa et al 1988;Lüscher et al 1992). It participates and plays a substantial role in the generation of various diseases like atherosclerosis (Ross 1993(Ross , 1999Heitzer et al 1996;Besler et al 2008;Heistad 2008), essential hypertension (Lüscher 1988;Vanhoutte 1992;Taddei et al 1995;Besler et al 2008), diabetes mellitus and diabetic vasculopathies (Makimattila et al 1996;Bakker et al 2009;Nathanson and Nyström 2009), chronic obstructive pulmonary disease -COPD (Peinado et al 2008), rheumatoid arthritis (Hansel et al 2003;Szekanecz and Koch 2008), psoriatic arthritis (Gonzalez-Juanatey et al 2007), osteoarthritis (Miller et al 2007), ankylosing spondylitis (Sari et al 2006), systemic lupus erythematosus (Piper et al 2007), cancer metastasis (Johansson et al 2010;Takala et al 2010), migraine and stroke (Besler et al 2008;Elliott 2008), anaphylactic and traumatic shock (Menardi et al 2006;Shi et al 2007;Nakashidze 2009), systemic inflammatory response syndrome (Neary and Redmond 1999;Hingorani et al 2000;Menardi et al 2006), NO-induced vasoplegia in sepsis (Stawicki et al 2008;Funk et al 2009) and cardiac surgery …”
Section: The Endotheliummentioning
confidence: 99%
“…However, endothelial NO synthase and neuronal NO synthase are found in the order of nanomolar [11,12]. Moreover, iNOS expression has been found in most tumor tissues specimens and cultured tumor cells [13][14][15][16][17][18][19][20], suggesting a role for iNOS in cancer development and progression. However, there are few studies focusing on iNOS expression and its correlation with angiogenesis and lymphangiogenesis in GC.…”
Section: Introductionmentioning
confidence: 98%